9: the answer is 4 to 13
10: the answer is 6 to 13
Either B or D I’m not really sure but I know it’s one of this answers
Answer:
C.
Step-by-step explanation:
-3 7/8 rounds down to -4
4.63 rounds up to 5
-4 x 6 + 5
-24 + 5
-19
her answer (-19.14) also rounds to -19
So yes, it is reasonable and the correct response is C.
Answer:
x
=
√
y
+
5
3
Explanation:
To find the inverse of a function expressed as
XXX
y
=
an expression in
x
rearrange the expression into the form:
XXX
x
=
an expression in
y
Given
XXX
y
=
3
x
2
−
5
Switch sides and add
5
to both sides
XXX
3
x
2
=
y
+
5
Divide both sides by
3
XXX
x
2
=
y
+
5
3
Take the square root of both sides
XXX
x
=
±
√
y
+
5
3
Since we were asked for an inverse function, I've eliminated the non-primary root (a function can not have two values for a single argument value).
Therefore
XXX
x
=
instead of Y do G
Step-by-step explanation: